PENGARUH PERBANDINGAN TERIGU DENGAN PUREE LABU KUNING (Cucurbita moschata ex. Poir) TERHADAP KARAKTERISTIK KUE LUMPUR - Agustin, Vennyta; Sugitha, I Made; Ari Sandhi W, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 6 No 2 (2017): Jurnal ITEPA, 2017)
The research aims to determine the effect of the comparison ofwheat flour with pumpkin (Cucurbita moschata ex. Poir) puree on the characteristics of “kue lumpur” and to determine the right ratio of pumpkin puree and wheat flour to produce “kue lumpur” with the best characteristics. The research using Completely Randomized Design with 5 treatments of ratio between pumpkin puree with wheat flour, namely : 100% wheat flour and 0% pumpkin puree, 90% wheat flour and 10% pumpkin puree, 80% wheat flour and 20% pumpkin puree, 70% wheat flour and 30% pumpkin puree, and 60% wheat flour and 40% pumpkin puree. Each treatment was repeated three times to obtain 15 experimental units. Data being acquired would be analyzed with variance analysis and if there was an effect to the variables being examined, then it would be continued with Duncan test. The result of research showed that the ratio of 70% wheat flour and 30% pumpkin puree resulted in the best “kue lumpur” characteristic with 43,33% water content, 0,70% ash, 3,88% protein, 28,67% fat, 23,42% carbohydrate, and 142,21 ?g/gbeta carotene. For sensory evaluation, thecolor scoring (yellow rather orange), color hedonic (like), flavor scoring (rather typical pumpkin), flavor hedonic (like), texture scoring (soft), texture hedonic (like), taste scoring (typical pumpkin), taste hedonic (like) and overall acceptance (like).